Inferred global connectivity of whale shark Rhincodon typus populations. Issue 2 (29th January 2013) - Sequeira, A. M. M.; Mellin, C.; Meekan, M. G.; Sims, D. W.; Bradshaw, C. J. A.
<x xml:space="preserve">Abstract</x> Ten years have passed since the last synopsis of whale shark Rhincodon typus biogeography. While a recent review of the species' biology and ecology summarized the vast data collected since then, it is clear that information on population geographic connectivity, migration and demography of R. typus is still limited and scattered. Understanding R. typus migratory behaviour is central to its conservation management considering the genetic evidence suggesting local aggregations are connected at the generational scale over entire ocean basins. By collating available data on sightings, tracked movements and distribution information, this review provides evidence for the hypothesis of broad‐scale connectivity among populations, and generates a model describing how the world's R. typus are part of a single, global meta‐population. Rhincodon typus occurrence timings and distribution patterns make possible a connection between several aggregation sites in the Indian Ocean. The present conceptual model and validating data lend support to the hypothesis that R. typus are able to move among the three largest ocean basins with a minimum total travelling time of around 2–4 years. The model provides a worldwide perspective of possible R. typus migration routes, and suggests a modified focus for additional research to test its predictions. The framework can be used to trim the hypotheses for R. typus movements and aggregation timings, thereby isolating possible mating and breeding areas that are currently unknown. This will assist endeavours to predict the longer‐term response of the species to ocean warming and changing patterns of human‐induced mortality.